EVALUATION OF ANAEROBIC ABILITIES OF STUDENTS APPLYING THE RUNNING ANAEROBIC SPRINT TEST - Ratko Pavlović,; Kemal Idrizović,; Martin Pupiš, (Sport Scientific And Practical Aspects, 2025)
Anaerobic abilities participate in most activities that are characterized by high intensity and short duration of activity. This type of endurance is the dominant activity in submaximal and maximal intensity. Conditioned by the good functioning of the cardiovascular and respiratory systems, morphological status, metabolism, muscle structure, etc. The research has conducted with the aim of evaluating anaerobic abilities of students of the Faculty of Physical Education and Sport of East Sarajevo and Nikšić applying Running Anaerobic Sprint Test (RAST). The sample included a total of 40 male students, including 20 students from Eastern Sarajevo (age 21±0,5 years, average weight 76,69 ± 6,61kg) and (20 students from Nikšić (age 21±0,5 years, the average weight 79,40±9,66kg). The results showed almost identical values of anaerobic capacity of students who are expected for this population with little benefits students of East Sarajevo. The average strength of the lower extremities student East Sarajevo amounted to 594,79 W, compared to the students of the Nikšić 579,15 W, which is a slight difference that is not statistically significant. A slightly higher average index of fatigue was recorded with students of Nikšić from (FI=8,20) suggesting a weaker state of anaerobic capacity in relation to the pattern of East Sarajevo, or lower tolerance to lactate.